The Political Economy of Workplace Injury in Canada - Bob Barnetson (Fabriks: Studies in the Working Class, 2010)
Workplace injuries are common, avoidable, and unacceptable. The Political Economy of Workplace Injury in Canada reveals how employers and governments engage in ineffective injury prevention efforts, intervening only when necessary to maintain the standard legitimacy. Dr. Bob Barnetson sheds light on this faulty system, highlighting the way in which employers create dangerous work environments yet pour billions of dollars into compensation and treatment. Examining this dynamic clarifies the way in which production costs are passed on to workers in the form of workplace injuries.